Natural language question and answer system on semantic health website - Handayani, Dini; Kartiwi, Mira (IIUM Press, 2015)

(untitled)
Web search by using generic search engines is the most common activity on the Web. Despite a wide range of information one could gathered from the Internet, there has not been many websites reported providing facility for the user to query the information using a natural language. It is the aim of this research to develop a prototype that implements query technique based on natural language processing to answer such query, extraction and summarization technique to automatically generate paragraph level for a better time saving process. In early 2007, Cervical Cancer Organization reported that a female-related disease, particularly cervical cancer, is the 5th most common cancer in women worldwide. According to that report, the aim of this research is to ensure that the web-based tool developed in this study facilitate the knowledge sharing activities among medical practitioners and public users.